Chronic Fatigue Syndrome/Myalgic Encephalomyelitis Diagnosis and Treatment - Ricevuti, Giovanni; Lorusso, Lorenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue on CFS/ME collects 18 papers with an interdisciplinary view on the current demographic and epidemiological data and immunological characteristics of CFS/ME and examines the different pathogenic hypotheses, as well as giving information about the latest knowledge on diagnostic investigations, pharmacological, integrative, physical, cognitive-behavioral and psychological curative approaches.